Determination of Reactivity Ratios of Copolymerization of Acrylamide (Am) and Methacryloxyethyltrimethyl Ammonium Chloride (Dmc) with Ultraviolet Initiation, and Their Sequence Length Distribution. Issue 5 (June 2016) - Wang, Yonghong; Zhang, Xinru; Li, Wanjie; Cheng, Jialiang; Liu, Chengcen; Zheng, Jiajun
The copolymer P(AM-DMC), one kind of cationic polyacrylamide, was synthesized by using acrylamide (AM) and methacryloxyethyltrimethyl ammonium chloride (DMC) as monomers with ultraviolet initiation. The copolymer was characterized by Fourier transform infrared spectroscopy. The composition of the copolymer was determined from the chlorine content by silver nitrate titration. The effects of monomer feed ratio and conversion on the composition of copolymer were discussed. Reactivity ratios were determined by the Fineman-Ross, Kelen-Tudos and Yezrielev-Brokhina-Roskin methods, indicating that their positive order calculation results were very different with those of reverse order, when the reactivity ratios were determined by Fineman-Ross. However, their positive order and reverse order calculation results were similar when the reactivity ratios were determined by the Kelen-Tudos and Yezrielev-Brokhina-Roskin methods. Therefore, the reactivity ratios were determined using the average results of the Kelen-Tudos and Yezrielev-Brokhina-Roskin methods. The reactivity ratios of AM and DMC were 2.3398 and 0.2285, respectively. This result showed that the copolymerization of AM and DMC was a non-ideal random copolymerization. Furthermore, the content of AM segments decreased with the increase of AM feed content, but the content of DMC segments increased. Moreover, the sequence length distribution was irregular and narrow, because AM was prone to homopolymerization.